Phytoextraction of lead and its relationship with histidine in six plant species using ICP-MS and HPLC-MS - Ozen, Sukran Akkus; Yaman, Mehmet (Taylor & Francis Ltd, 2016)
High-performance liquid chromatography-mass spectrometry and inductively coupled plasma mass spectrometer (ICP-MS) methods were used for determination of histidine and lead in leaves of six plant species taken from industrial areas, including Gaziantep and Bursa cities, Turkey. For extraction of histidine from plant samples, ultrapure water was used at 90 degrees C for 30min. Using optimum conditions of 0.2mLmin(-1), 70V, 15 mu L and 20 degrees C, concentrations of histidine (in mgkg(-1)) were found to be between 2 and 9 for Morus L., 6 and 13 for Robinia pseudoacacio L., 2 and 10 for Populous nigra L., 3 and 10 for Thuja, 1 and 11 for Cupressus arizonica and 4 for Cedrus libani. Concentrations of lead were in the ranges of 4-378mgkg(-1) for Morus L., 1-122mgkg(-1) for R. pseudoacacio L., 1-14mgkg(-1) for P. nigra L., 1.6-224mgkg(-1) for Thuja (Cupressaceae), 1.5-57mgkg(-1) for C. arizonica and 1.8mgkg(-1) for C. libani. Related with correlation coefficient, significant linear correlation for Thuja (Cupressaceae) (r=0.81) and insignificant linear correlation for P. nigra L. (r=0.50) were seen. Further, the leaves of Morus L., Thuja and R. pseudoacacio L. have a potential as biomonitor and/or hyperaccumulator for Pb because the rates of their maximum/minimum concentrations were found higher than 90.
Keywords: Histidine; lead; hyperaccumulator plants; phytoremediation; ICP-MS; HPLC-MS